Житиейный текст в «Соборнике» Нила Сорского: перевод или пересказ? (The Vitae of Nil Sorskii’s “Sobornik”: Translation or Periphrasis?) - Lönngren, Tamara (Poljarnyj vestnik, 2003)
This paper attempts to show that Nil Sorskii, the author of the well-known three-volume "Sobornik", in compiling this collection of ancient Greek vitae used Greek texts as well as Slavonic translations. He compared the Slavonic texts with the Greek originals and corrected their difficult archaic language, thus turning it into the understandable simple Russian language of his own time.